The good luck of right now - Quick, Matthew, 1973- (Harper, 2014)
When his mother dies, 38-year-old Bartholomew Neil, who doesn't know how to be on his own, discovers a letter in his mother's underwear drawer that causes him to write a series of highly intimate letters to actor Richard Gere, while embarking on a quest to find out where he belongs.